Reproductive Health in the View of the Toba Batak Ethnicity - Aulia, Farid; Sitinjak, Alfredo Agusto; Derista, Dea; Prianggina, Nazifa; Zahra, Fifi Haifa; Muhammad Rizky1 (Indonesian Journal of Medical Anthropology, 2023)
Reproductive health is a complete physical, mental and social well-being in all matters including the reproductive system and function, and the reproductive process and is not just a condition that is free from disease and disability. Everyone must be able to have a satisfying and safe sexual life for himself, also be able to reduce and fulfill his desires without any obstacles, when, and how often to have children. Inland communities who are still lacking in understanding reproductive health knowledge and lack of adequate facilities for health checks, enhance adolescents’ understanding of the process of change that occurs in themselves, especially young women facing menarche, need to provide health information and also understanding from their closest people, family and friends. the social environment becomes a support system. The importance of receiving news about early menopause and how to deal with early menopause so that there is no excessive anxiety.